Reliability and validity of intravaginal pressure measurements with a new intravaginal pressure device: The FemFit®. Issue 1 (6th October 2019) - Cacciari, Licia P.; Kruger, Jennifer; Goodman, Jonathan; Budgett, David; Dumoulin, Chantal
Abstract: Aims: To test the reliability and validity of intravaginal pressure measurements acquired during pelvic floor muscle (PFM) tasks in different body positions using the FemFit®, a new intravaginal pressure device. Methods: Twenty healthy adult women participated in this study. Two assessment sessions were conducted. Intravaginal pressure measurements using the FemFit® were repeated during PFM contraction and straining maneuvers while lying and standing. Maximal intravaginal pressures were collated and compared within and between sessions. They were also correlated to maximal force measurements obtained by dynamometry and vaginal digital palpation. Test‐retest reliability was assessed using intraclass correlation coefficient, standard error of measurement and Bland‐Altman plots. The validity of the pressure measurements was assessed using Pearson's correlation (dynamometry) and Spearman's rho (palpation). Results: This test‐retest study indicate excellent reliability for PFM contraction and straining maneuver both in lying and standing, within and between sessions. For the straining maneuver while standing, increased variability was suggested by a wider limit of agreement on Bland‐Altman plots (spanning 31.3 to 43.3mm Hg). A significant moderate to strong correlation was found when comparing measurements of PFM contraction using the FemFit® and the dynamometer or the palpation (Pearson's coefficient = 0.72, P  = .006; Spearman's rho = 0.68, P  = .005, respectively). Conclusion: Our research findings suggest that intravaginal pressures can be reliably measured during PFM contraction and straining manoeuver while lying and standing, using the FemFit® device, both within and between sessions. A moderate to strong correlation between the FemFit® pressure and the force measurements obtained by dynamometry or palpation reinforce the validity of measurements.